2020
DOI: 10.1002/qua.26398
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of ferrocene topology under various temperatures

Abstract: We present the first quantum mechanical Atom-Centered Density-Matrix Propagation molecular dynamic (MD) study to investigate ferrocene (Fc) conformation in gas phase. The MD simulations were performed at several temperatures (7, 18, 80, 120, 180, 293, and 500 K) for a period of 10 ps. It is found that, at very low temperatures (≤18 K), ferrocene prefers eclipsed-like conformation. At higher temperatures (>18 K), the cyclopentadienyl rings (Cp) of ferrocene exhibit apparent fluxional rotations, leading to confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 44 publications
4
13
0
Order By: Relevance
“…Kaspi-Kaneti and Tuvi-Arad further indicated that the symmetry transition point cusp at 18° represents the point at which the molecular geometry has an equal distance from an eclipsed and staggered Fc [11]. These conclusions are confirmed by our most recent first principle molecular dynamics study [12] which also revealed that conformational changes of ferrocene with temperature and confirmed by the most recent study when Fc crystallised with hexafluorobenzene of Bear et al [13].…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Kaspi-Kaneti and Tuvi-Arad further indicated that the symmetry transition point cusp at 18° represents the point at which the molecular geometry has an equal distance from an eclipsed and staggered Fc [11]. These conclusions are confirmed by our most recent first principle molecular dynamics study [12] which also revealed that conformational changes of ferrocene with temperature and confirmed by the most recent study when Fc crystallised with hexafluorobenzene of Bear et al [13].…”
Section: Introductionsupporting
confidence: 68%
“…1) exhibit eclipsed and staggered conformers with small energy differences [8,10,24]. The stability of staggered and eclipsed Fc conformers has been subjected to debate since the discovery some seventy years ago until very recently [6-8, 10, 12], when a series of combined experiment and theoretical research has provided compelling evidences that the eclipsed Fc in very low temperatures (under 18 K) is the more stable conformer [7,10,12]. Fc does not become a mixture of both eclipsed and staggered conformers [11], nor does it become an orientation with a mean rotation angle along the reaction coordinate.…”
Section: Geometry and Conformer Stability From Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…(2003), the measurement at 150 K does not show apparent differences from the IR spectrum measured in very low temperature of Duggan et al(49). Figures2(a) and (b) compare the calculated IR spectra of Fc and *Fc in the eclipsed and staggered conformer forms, respectively using the same DFT methods.…”
mentioning
confidence: 78%
“…The IR of *Fc but splits into two well-separated peaks at ca 1035 cm -1 and 1141 cm -1 , respectively. The former (1035 cm -1 ) for the Cp in-plane stretching turtle swimming (49)) and the latter (1141 cm -1 ) for the opposite Cp ring breathing (small-large). The IR spectral band with largest frequency at around 3100-3200 cm -1 , refers to vibrations of the C-H stretches of the molecules.…”
Section: Ir Spectral Response To Methylation Of the Cp Ringsmentioning
confidence: 98%